2007
DOI: 10.1177/1359105307074253
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Processes of Exercise Behaviour Change Associated with Movement through the Stages of Exercise Behaviour Change

Abstract: This longitudinal study identified processes of exercise behaviour change (POC) associated with movement between the stages of exercise behaviour change (SOC). Participants' (N = 312) physical activity, SOC and POC were recorded at baseline, one, three, six and 12 months post-test. Following baseline, participants received one of three physical activity interventions. The process of self-liberation was important at each stage movement. The process of stimulus control appeared important when progressing from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
2
25
1
Order By: Relevance
“…These results are also consistent with past TTM research in the exercise domain, as the use of the behavioral processes of change have generally been shown to increase through the action stage before leveling off at the maintenance stage (Fallon, Hausenblas, & Nigg, 2005;Marshall & Biddle, 2001;Marcus et al, 1992). Furthermore, Lowther et al (2007) conducted a longitudinal study of process of change use and reported the transition from contemplation to preparation was predicted by increased use in processes of change, whereas moving into behavioral action was predicted by increased use in self-liberation. As such, prior to the implementation of PST interventions, sport psychology professionals should consider the commitment level of the athlete as it relates to their mental training, as well as athletes' confidence in their ability to adhere to a PST routine.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are also consistent with past TTM research in the exercise domain, as the use of the behavioral processes of change have generally been shown to increase through the action stage before leveling off at the maintenance stage (Fallon, Hausenblas, & Nigg, 2005;Marshall & Biddle, 2001;Marcus et al, 1992). Furthermore, Lowther et al (2007) conducted a longitudinal study of process of change use and reported the transition from contemplation to preparation was predicted by increased use in processes of change, whereas moving into behavioral action was predicted by increased use in self-liberation. As such, prior to the implementation of PST interventions, sport psychology professionals should consider the commitment level of the athlete as it relates to their mental training, as well as athletes' confidence in their ability to adhere to a PST routine.…”
Section: Discussionsupporting
confidence: 90%
“…To determine statistical significance an alpha level of .05 was used. Based on the literature examining exercise behavior change (e.g., Lowther et al, 2007;Marcus et al, 1992;Marshall & Biddle, 2001) a series of one-way analyses of variance (ANOVAs) were conducted with Sheff e post hoc comparisons to examine the following hypotheses: (1) the use of the processes of change will be significantly less in precontemplation than in any other stage of change; (2) the use of the behavioral processes of change will be significantly greater in action and maintenance than in pre-action stages of change (i.e., precontemplation, contemplation); (3) the use of the experiential processes of change will be significantly less in maintenance than in action; and (4) the use of the experiential processes of change will peak in the action stage.…”
Section: Construct Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, according to a study conducted in England, 72% of English, 69% of Irish, and 69% of Scottish people are not physically active. Similarly, according to statistics from health scans conducted in Canada, 47.8% of the population is identified as inactive during leisure time (Lowther, Mutrie & Scott, 2007). An extensive study with the participation of 23 countries by Haase, Steptoe, Sallis and Wardle (2004) revealed that college students do not engage in physical activities at recommended levels.…”
Section: Introductionmentioning
confidence: 99%
“…Introjected regulation 1 underlies behavior for those feeling compelled to take in physical activity to avoid aversive 2 feeling states (e.g., guilt over skipping a workout) or to experience ego-affirming states (e.g., 3 pride in fitness). The behavior of exercisers who participate in activity for benefits of 4 exercise, and assign personal importance to engagement of regular physical activity, is said to 5 be governed by identified regulations.…”
mentioning
confidence: 99%